Hypothesis: bipolar disorder is an Epstein–Barr virus‐driven chronic autoimmune disease – implications for immunotherapy. Issue 4 (6th April 2020) - Pender, Michael P
Abstract: Bipolar disorder (BD) is a chronic disease characterised by episodes of major depression and episodes of mania or hypomania, with a worldwide prevalence of 2.4%. The cause of BD is unknown. Here, I propose the hypothesis that BD is a chronic autoimmune disease caused by Epstein–Barr virus (EBV) infection of autoreactive B cells. It is postulated that EBV‐infected autoreactive B cells accumulate in the brain where they provide costimulatory survival signals to autoreactive T cells and differentiate into plasma cells producing pathogenic autoantibodies targeting brain components such as the N‐methyl‐D‐aspartate receptor. It is also proposed that the accumulation of EBV‐infected autoreactive B cells in the brain is a consequence of a genetically determined defect in the ability of CD8 + T cells to control EBV infection. The theory is supported by studies indicating that autoimmunity, EBV infection and CD8 + T‐cell deficiency all have roles in the pathogenesis of BD. According to the hypothesis, BD should be able to be treated by EBV‐specific T‐cell therapy and to be prevented by vaccination against EBV in early childhood. Exposure to sunlight or appropriate artificial light should also be beneficial in BD by augmenting CD8 + T‐cell control of EBV infection. Abstract : This article proposes the novel hypothesis that bipolar disorder (BD) is a chronic autoimmune disease caused by Epstein–Barr virus (EBV) infection of autoreactive B cells, which accumulate in the brain where they facilitate an autoimmune attack on brain components such as the NMDA receptor. It is postulated that the accumulation of EBV‐infected autoreactive B cells in the brain is a consequence of a genetically determined defect in the ability of CD8 + T cells to control EBV infection. According to the hypothesis, BD should be able to be treated by EBV‐specific T‐cell therapy and to be prevented by vaccination against EBV early in life.